Host Defence to Pulmonary Mycosis - Christopher H Mody; Peter W Warren (Canadian Journal of Infectious Diseases)
OBJECTIVE: To provide a basic understanding of the mechanisms of host defense to pathogenic fungi. This will help physicians understand why some patients are predisposed to fungal infections and update basic scientists on how microbial immunology applies to fungal disease.